The Perspective of Man in Islam and Christianity - Fathor Rasi (Budapest International Research and Critics University, 2019)
The aim of this study is to know the perspective of man in Islam and Christianity. The essence of human can be comprehend only through intuitive reason which is called intellectual or the Eye of Hurt (in Arabic word ‘ayn al-qalb) rather than merely rely on discursive reason or the ratio. An effort to revive the divine dimensions in the hearts and behavior of modern man is very important to create a harmony and god relation between man and nature. Modern man has already melted in the mud of is his daily life and it’s almost impossible to be near to the Spirit of his Lord. It can be concluded that any assessments, interpretations of all events and human phenomena cannot be accepted if placing human as a marginal entity or rim. By stating that man is a small nature (microcosm) and the nature is large man (the macrocosm) which has been direct manifestation of God's names, it has a significant meaning to the perspective and the relationship between God, nature and humankind.